2019
DOI: 10.18295/squmj.2018.18.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Rate and Predictors of Publication of Resident Abstracts Presented at Oman Medical Specialty Board Scientific Meetings

Abstract: Objectives: This study aimed to examine the rate and factors associated with the publication of abstracts presented by residents at Oman Medical Specialty Board (OMSB) scientific meetings. Methods: This retrospective study was performed in February 2018. Two previous national OMSB scientific meetings at which resident abstracts were presented were identified, having taken place in January 2014 and December 2016, respectively. Independent searches of the MEDLINE® (National Library of Medicine, Bethesda, Marylan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…47 Similarly, less than one-quarter (8-22.1%) of research performed by OMSB residents has been found to result in peer-reviewed publications. 43,48 The Health Vision 2050 initiative of the Ministry of Health aspires for Oman to be "a regional leader and a research hub of international standards", with collaboration between local and international academic institutions recognised as a key factor in strengthening the country's research capacity. 39 However, although this mission acknowledges that establishing a career path for research-oriented professionals is an important factor in improving research quality and quantity, to the best of the authors' knowledge, no well-defined research training pathways have as yet been established in Oman.…”
Section: S U M M E R R E S E a R C H S T U D E N T S H I P Smentioning
confidence: 99%
See 2 more Smart Citations
“…47 Similarly, less than one-quarter (8-22.1%) of research performed by OMSB residents has been found to result in peer-reviewed publications. 43,48 The Health Vision 2050 initiative of the Ministry of Health aspires for Oman to be "a regional leader and a research hub of international standards", with collaboration between local and international academic institutions recognised as a key factor in strengthening the country's research capacity. 39 However, although this mission acknowledges that establishing a career path for research-oriented professionals is an important factor in improving research quality and quantity, to the best of the authors' knowledge, no well-defined research training pathways have as yet been established in Oman.…”
Section: S U M M E R R E S E a R C H S T U D E N T S H I P Smentioning
confidence: 99%
“… 47 Similarly, less than one-quarter (8–22.1%) of research performed by OMSB residents has been found to result in peer-reviewed publications. 43 , 48 …”
Section: Framework For Implementation In Omanmentioning
confidence: 99%
See 1 more Smart Citation